Application of Neuromodular Techniques for Correction of Personality Characteristics in the Course of Transactional Analysis - D B Chaivanov; Y A Chudina (RUDN Journal of Psychology and Pedagogics, 2011)
The probability of using neuromodulation methods and creating instrumental equivalent of transactional analysis used for ego-states correction is discussed in the article. Ego-states are analyzed in accordance with neuro-cognitive mechanisms and psycho-functional states.